Find f(1), f (2), f (3), and f (4) if f (n) is defined recursively by f (0) = 1 and for n = 0, 1, 2,a) f (n + 1) =f (n) + 2.b) f (n + 1) =3 f (n).c) f (n+ 1) = 2 f (n).d) f (n+ 1) = f (n)2 + f (n)+ 1.

Leslie Ogu COMM 1041 10/27/2016 - Group and Team Dynamics Homework ➢ By tonight - nonverbal or technology paper ➢ By 11/1: ○ Read Chapter 7 ○ Read the articles she sends out and be prepared to discuss ○ Find a print ad that plays on your emotions and bring it in. Be prepared to talk about it Team Teaching Project ➢ Need...